2018
DOI: 10.1021/acs.est.7b06357
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Spent Cr Adsorbents as Catalyst for Eliminating Methylmercaptan

Abstract: Waste adsorbents generated from treating Cr(VI)-containing wastewater are hazardous materials and generally landfilled or treated by acid or base desorption, with concomitant high cost and toxic effects. The present work shows that these Cr adsorbents can be reused as highly efficient catalysts for treating sulfur-containing VOCs (CHSH), not only avoiding the economic and environmental impact from the conventional approaches, but also achieving the efficient treatment of sulfur-containing waste gas. Importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Thus, it could be concluded that the poor dispersion of Cr species over the 15Cr/MCM‐41 catalyst gives rise to the formation of isolated Cr(VI) states. In fact, it's worth mentioning that another method for the synthesis of Cr/MCM‐41 catalyst, called as Chromium Column Adsorption process and reported in our previous work, shows a better dispersion of Cr species over the Cr/MCM‐41 sample, as displayed in Figure S6 in ESI (according to the XRF data, the Cr content from this method is close to 15 %wt, results are not shown). Surprisingly, no characterization of the isolated state of Cr(VI) species are seen from the H 2 ‐TPR profile (as shown in Figure S7B in ESI), and meanwhile, its activity towards PDH reaction is higher than that over the 15Cr/MCM‐41 sample, as exhibited in Figure S7A in ESI).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, it could be concluded that the poor dispersion of Cr species over the 15Cr/MCM‐41 catalyst gives rise to the formation of isolated Cr(VI) states. In fact, it's worth mentioning that another method for the synthesis of Cr/MCM‐41 catalyst, called as Chromium Column Adsorption process and reported in our previous work, shows a better dispersion of Cr species over the Cr/MCM‐41 sample, as displayed in Figure S6 in ESI (according to the XRF data, the Cr content from this method is close to 15 %wt, results are not shown). Surprisingly, no characterization of the isolated state of Cr(VI) species are seen from the H 2 ‐TPR profile (as shown in Figure S7B in ESI), and meanwhile, its activity towards PDH reaction is higher than that over the 15Cr/MCM‐41 sample, as exhibited in Figure S7A in ESI).…”
Section: Resultsmentioning
confidence: 77%
“…The mesoporous MCM‐41 was prepared in our laboratory as previously reported . The Cr modified MCM‐41 catalysts with different weight of Cr loadings (5, 10, and 15 wt%) were synthesized by the wet impregnation method, due to its superiority of low cost and operational easy.…”
Section: Methodsmentioning
confidence: 99%
“…One attractive option for dealing with these undesired Cr adsorbents is to recycle them as highly efficient catalysts. 10 In fact, the outstanding characteristic of the present Cr adsorbent, regarded as organic−inorganic hybrid silicon material, is its calcined product, which can eventually become MCM-41, and is known to be a catalyst support for many heterogeneous catalysts. As a matter of fact, waste Cr adsorbents were recycled by calcination and reused as Cr/MCM-41 catalyst to eliminate methyl mercaptan (CH 3 SH), a typical compound of sulfur-containing VOCs, 11,12 as shown in our recent study, 10 which indicates a new avenue of green chemistry and has important implications for environmental protection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 In fact, the outstanding characteristic of the present Cr adsorbent, regarded as organic−inorganic hybrid silicon material, is its calcined product, which can eventually become MCM-41, and is known to be a catalyst support for many heterogeneous catalysts. As a matter of fact, waste Cr adsorbents were recycled by calcination and reused as Cr/MCM-41 catalyst to eliminate methyl mercaptan (CH 3 SH), a typical compound of sulfur-containing VOCs, 11,12 as shown in our recent study, 10 which indicates a new avenue of green chemistry and has important implications for environmental protection. However, it was proposed to use the chemical reagent K 2 Cr 2 O 7 to prepare Cr(VI)-containing solutions, and the influence of any additional impurity ions was not considered, so the results might not be applicable for real spent Cr adsorbents, because many other chemical species in a given wastewater would be coadsorbed or/and compete for adsorption with Cr on the adsorbent during wastewater treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation